Polar vortex : a family memoir - Dorrance (The Experiment, 2024)
"For fans of Can't We Talk About Something More Pleasant?, a poignant, stirring graphic memoir--both heartbreaking and darkly funny--that perfectly captures the grief, nostalgia, and chaos of traveling home to care for an elderly parent in crisis" -